2018
DOI: 10.17675/2305-6894-2018-7-3-7
|View full text |Cite
|
Sign up to set email alerts
|

A potentiometric study of an H2SO4–H3PO4–H2O system containing Fe(III) and Fe(II) cations

Abstract: The potentiometric method was used to study an H 2 SO 4 -H 3 PO 4 -H 2 O system (20-95°C) containing Fe(III) and Fe(II) cations. The oxidizing ability of the 2 M H 2 SO 4 + H 3 PO 4 system containing Fe(III) and Fe(II) (1:1) decreases as the molar fraction of H 3 PO 4 increases. The observed effect results from the formation of Fe(III) complexes with phosphate anions that are weaker oxidants than the corresponding hydrate and sulfate complexes. Variation in the total content of the equimolar Fe(III) + Fe(II) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In fact, a potentiometric study of E 0 Fe(III)/Fe(II) in various acids confirmed this. For mineral acids containing Fe(III), the oxidation capacity decreases in the series HClO 4  HBr  H 2 SO 4  HCl  H 3 PO 4  HF [165]. The prospects of practical use of HF for reducing the oxidation capability of media containing Fe(III) are very limited due to the high toxicity of this acid.…”
Section: Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a potentiometric study of E 0 Fe(III)/Fe(II) in various acids confirmed this. For mineral acids containing Fe(III), the oxidation capacity decreases in the series HClO 4  HBr  H 2 SO 4  HCl  H 3 PO 4  HF [165]. The prospects of practical use of HF for reducing the oxidation capability of media containing Fe(III) are very limited due to the high toxicity of this acid.…”
Section: Ligandsmentioning
confidence: 99%
“…It is important that addition of H 3 PO 4 to solutions of acids (HCl and H 2 SO 4 ), which do not considerably decrease the oxidation properties of Fe(III) cations, significantly decreases the oxidation capacity of these systems. In solutions of acid mixtures (HCl + H 3 PO 4 or H 2 SO 4 + H 3 PO 4 ) containing Fe(III) salts, the oxidation capability decreases with an increase in the relative content of H 3 PO 4 in the system [165,166]. In addition, examination of the system H 2 SO 4 -H 3 PO 4 -H 2 O-Fe(III) by cyclic voltammetry (CVA) shows that binding Fe(III) ions into phosphate complexes significantly decreases the rate of their diffusion in a corrosion environment [167].…”
Section: Ligandsmentioning
confidence: 99%
“…Previously, the potentiometry method was used to study an H 2 SO 4 -H 3 PO 4 -H 2 O system containing Fe(III) and Fe(II) cations [5,6]. It was shown that a probable reason of the efficient protection of mild steel by triazole-based composite inhibitors in H 3 PO 4 or its mixtures with H 2 SO 4 containing Fe(III), in comparison with similar solutions of H 2 SO 4 alone, is that phosphate complexes of Fe(III) are formed in these media.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic voltammograms of platinum electrode in 2.0 M H 2 SO 4 + Fe 2 (SO 4 ) 3 at different concentration of Fe(III). Scan rate: 0.10 Vs -1 at 25C.The values of current maxima on the current-potential curves is determined by the Randles-Sevcik equation: 69105 is the equation constant at 25C; z is the number of electrons participating in the redox process (z = 1 for the redox pair Fe (III)/Fe (III)); S is the surface area of the electrode (m 2 ); C is the concentration of the electrochemically active substance (molm -3 ); D is the diffusion coefficient (m 2 •s -1 ); and v is the potential sweep rate (V•s -1 ). The Randles-Sevcik equation describes redox processes that occur in equilibrium systems.…”
mentioning
confidence: 99%
“…It was previously shown [6] that a decrease in the oxidizing ability of acids containing Fe(III) salts makes it possible to effectively use corrosion inhibitors in these environments to protect mild steel. A decrease in the oxidizing ability of these solutions is possible by binding these cations into complex compounds, which have a lower oxidizing potential in comparison with hydrated Fe(III) ions.…”
mentioning
confidence: 99%